Copy number variant analysis from exome data in 349 patients with epileptic encephalopathy. Issue 2 (1st July 2015) - Epilepsy Phenome/Genome Project & Epi4K Consortium; Allen, Andrew S.; Berkovic, Samuel F.; Coe, Bradley P.; Cook, Joseph; Cossette, Patrick; Delanty, Norman; Dlugos, Dennis; Eichler, Evan E.; Epstein, Michael P.; Glauser, Tracy; Goldstein, David B.; et al.
<x xml:space="preserve">Abstract</x> Infantile spasms (IS) and Lennox–Gastaut syndrome (LGS) are epileptic encephalopathies characterized by early onset, intractable seizures, and poor developmental outcomes. De novo sequence mutations and copy number variants (CNVs) are causative in a subset of cases. We used exome sequence data in 349 trios with IS or LGS to identify putative de novo CNVs. We confirm 18 de novo CNVs in 17 patients (4.8%), 10 of which are likely pathogenic, giving a firm genetic diagnosis for 2.9% of patients. Confirmation of exome‐predicted CNVs by array‐based methods is still required due to false‐positive rates of prediction algorithms. Our exome‐based results are consistent with recent array‐based studies in similar cohorts and highlight novel candidate genes for IS and LGS. Ann Neurol 2015;78:323–328